2012
DOI: 10.1111/j.1365-246x.2012.05504.x
|View full text |Cite
|
Sign up to set email alerts
|

Laplace-domain waveform inversion versus refraction-traveltime tomography

Abstract: SUMMARY Geophysicists and applied mathematicians have proposed a rich suite of long‐wavelength velocity estimation algorithms to construct starting velocity models for subsequent pre‐stack depth migration and inversion. Refraction‐traveltime tomography derives subsurface velocity models from picked first‐arrival traveltimes. In contrast, Laplace‐domain waveform inversion recovers long‐wavelength velocity structure using the weighted amplitudes of first and later arrivals. There are several implementations of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In previous research, the LFWI algorithm was verified for constructing meaningful velocity models from seismic field data sets by comparing it with other waveform inversion algorithms (Bae et al., 2012; Ha & Shin 2012; Kang et al., 2012; Shin et al., 2010). Especially, the LFWI algorithm is known for working well with inversion targets such as salt domes with significantly higher velocities than the surrounding sediment or rapidly changing velocity areas.…”
Section: Review Of the Laplace‐domain Full‐waveform Inversion Methodsmentioning
confidence: 99%
“…In previous research, the LFWI algorithm was verified for constructing meaningful velocity models from seismic field data sets by comparing it with other waveform inversion algorithms (Bae et al., 2012; Ha & Shin 2012; Kang et al., 2012; Shin et al., 2010). Especially, the LFWI algorithm is known for working well with inversion targets such as salt domes with significantly higher velocities than the surrounding sediment or rapidly changing velocity areas.…”
Section: Review Of the Laplace‐domain Full‐waveform Inversion Methodsmentioning
confidence: 99%
“…The application of the Laplace and Laplace‐Fourier transforms to seismic inversion has been documented in numerous publications [e.g., Shin and Cha , , ; Ha et al , , ; Bae et al , ]. Here we provide a brief overview of the method and refer the reader to the cited works for more details.…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity kernels of FVT are derived from the wave equation, and the traveltime of the main energy of the seismic wave is used, thus it can achieve better results than RFTT in both synthetic tests and field data processing. Bae et al (2012) compared the sensitivity kernels of FVT and Laplace FWI, and pointed out that Laplace FWI can reveal deeper structures than FVT even it is still using the first-arrival traveltime. Sheng et al (2006) showed that the first-arrival waveform contains little information of the deep structure, but it can be used to reconstruct the fine near-surface velocity structure.…”
Section: Introductionmentioning
confidence: 99%